Verso la prima legge sull’assistenza psichiatrica in Italia. Teorie e ideologie - Testa, Luana; Piazzi, AnDrea; Dario, Claudia (Il sogno della farfalla, 2008)
On the basis of the acquisitions of the most recent historiography and of a critique of readings inspired by the ideological position of the anti-psychiatry of the 60s, the Authors reconstruct the historical and political events and the scientific debate that led in 1904 to the enactment of the first Italian law on the assistance and cure of psychiatric patients, in the midst of great historical, social and cultural changes that involved the whole of Europe in the same period. The debate saw two opposing positions both of which generated by the flourishing positivist philosophy and by the need for scientificity which could oppose the magic-religious matrix: on the one hand German clinical practice based on Kraepelinian principles, on the other hand the degenerative theory of Morel perfectly integrated, in Italy, with the atavism of Lombroso. The latter theoretical position dominated and this gave rise to the principles which formed the basis of the law of 1904 and the subsequent development of Italian psychiatry.